RISK MANAGEMENT - AT THE CONVERGENCE BETWEEN PRUDENCE AND CONTINUITY, A BASIS FOR AN EFFICIENT GOVERNANCE - Gabriela-Geanina, TUDOSE; Grazia-Oana, PETROIANU (Strategii Manageriale)
The accountancy principles are sine qua non for a faithful image, nevertheless when it is about evaluation, accountancy is considered a source of uncertainty. The principle of being prudent is the pillar of accountancy having a view to protect the invested capital, although under the conditions of organizations development and of the desire to better results, which inevitably implies risk, this would infringe initiatives and change. Even more, prudence offers a continuity in organization activity, becoming accountancy fundamentals in the principles of corporation governance, the organization management respectively, by accepting the benefits of risk management, of financial management and internal control under the monitor of internal audit. The activity continuity is not only an accountancy principle but also an absolutely necessary element to quarantee the financial information. The principle of continuity also confers the accountancy science a provisional role because it extends its action from a simple elaboration of financial statements to the assurance of financial information to prevent difficulties, the finding and removal of risk and offering the necessary factors for an efficient provisional management. A good governance within a company reduces risks, increases performance, opens the way to financial markets, improves the marketing capacity for goods and services, the management style, shows transparency and social responsability.